Could a Caveman Do It? The Surprising Potential of Simple Attacks. - Perrone, L.F.
The research projects our investigations have spawned span topics in attack modeling, quantifying the effects of attacks on network performance and robustness, and the construction of computational tools for managing our simulation experiments. We hope, however, that our work's meta-contribution is to show, by proof of concept, that you must consider simple, sideways system attacks before you can rely on a system. We encourage engineers of mission-critical systems to look for then cavemen (or squirrels) and to study carefully what actions these adversaries might take against the products they roll out. In this paper we examine simple attacks on routing protocols for wireless networks. In our study, the system was to be a wireless ad hoc network, a collection of independent, possibly mobile computing devices that communicate using radio frequency technology.
Keywords: Computational tool; Mission-critical system; Mobile computing device; Network attack modeling; Network performance; Network security; Radio frequency technology; Routing protocol; Wireless ad hoc network